2021
DOI: 10.3389/fnins.2021.774585
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Stria Vascularis in the Pathogenesis of Sensorineural Hearing Loss: A Narrative Review

Abstract: Sensorineural hearing loss is a common sensory impairment in humans caused by abnormalities in the inner ear. The stria vascularis is regarded as a major cochlear structure that can independently degenerate and influence the degree of hearing loss. This review summarizes the current literature on the role of the stria vascularis in the pathogenesis of sensorineural hearing loss resulting from different etiologies, focusing on both molecular events and signaling pathways, and further attempts to explore the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 114 publications
0
10
0
1
Order By: Relevance
“…In previous studies in the experimental model, an oedema in stria vascularis was found [ 43 , 44 ] in mice with hypercholesterolemia [ 45 ]. Nevertheless, although stria vascularis is a well-known site of damage in systemic diseases, the actual underlying pathogenesis is still unknown [ 46 ]. We previously studied common markers shared between HL and ARHL in an experimental model, demonstrating that noise-induced hearing loss can worsen/accelerate redox status imbalance including the increase of reactive oxygen species production; lipid peroxidation; dysregulation of endogenous antioxidant response, vascular dysfunction, such as increased expression of hypoxia-inducible factor-1alpha and vascular endothelial growth factor in the cochlea, both of which are involved in the dysregulation of redox status and inflammatory pathway activation [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies in the experimental model, an oedema in stria vascularis was found [ 43 , 44 ] in mice with hypercholesterolemia [ 45 ]. Nevertheless, although stria vascularis is a well-known site of damage in systemic diseases, the actual underlying pathogenesis is still unknown [ 46 ]. We previously studied common markers shared between HL and ARHL in an experimental model, demonstrating that noise-induced hearing loss can worsen/accelerate redox status imbalance including the increase of reactive oxygen species production; lipid peroxidation; dysregulation of endogenous antioxidant response, vascular dysfunction, such as increased expression of hypoxia-inducible factor-1alpha and vascular endothelial growth factor in the cochlea, both of which are involved in the dysregulation of redox status and inflammatory pathway activation [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The slower rate of hair cell death in the nectin-3 KO cochlea might reflect the limited number of attached hair cells. The lateral wall of cochlea (stria vascularis) also contributes to auditory function and maintenance of homeostasis in the cochlear fluid through the generation of endocochlear potential (EP) ( Yu et al, 2021 ). The tight junction formation in the stria vascularis is important for the generation of EP ( Gow et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kolejnym bardzo poważnym zaburzeniem mogącym występować u osobników z umaszczeniem marmurkowym jest wrodzona głuchota (27), która zwykle rozwija się w ciągu pierwszych kilku tygodni po urodzeniu, gdy przewód słuchowy jest jeszcze zamknięty. Choroba spowodowana jest niedostateczną liczbą funkcjonalnych melanocytów w prążkowiu naczyniowym ślimaka, które są niezbędne do wytwarzania potencjału wewnątrz ślimakowego w uchu wewnętrznym, który umożliwia komórkom rzęskowym przekształcenie wibracji dźwiękowych w potencjał czynnościowy (40). Częstość występowania tego schorzenia u psów-nosicieli allelu M (genotyp heterozygotyczny 305 M/+) szacuje się na 3,5%, a u homozygot (M/M) na 25%.…”
Section: Typ Dziki Intensywna Pigmentacja Brak Wzoru Marmurkowegounclassified